Transformasi Lahan Pascatambang Di Taman Wisata Landak Menjadi Ekowisata Dengan Penerapan Pengelolaan Lingkungan Berkelanjutan - Marbun, Julianti; Manurung, Sondang Sylvia; Sianturi, Johnny Maruli Tua (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Landak Tourist Park was inaugurated in 2021 as a reclamation site for former mining land, covering an area of approximately 10 hectares, located near the residential areas between Mandor Village and Kayu Ara Village. The environmental restoration efforts at Landak Tourist Park are not yet optimal, as seen in the condition of the soil, water quality, and inadequate infrastructure. This study aims to assess the soil and water quality in environmental management, identify potential ecotourism types that can be developed, and evaluate the infrastructure and facilities at Landak Tourist Park. The research method used was mixed methods (observational description). The soil sample results indicate that the soil condition at Landak Tourist Park is below the minimum standard, with 20% of the soil being original, due to environmental degradation, which requires reclamation and quality improvement efforts. The water quality shows a decline, including increased turbidity, pH, BOD, COD, and TSS. A clean water treatment system is needed to supply clean water at Landak Tourist Park. The questionnaire results indicate that visitors to Landak Tourist Park are more interested in ecotrekking, nature tourism, environmental education, and nature conservation. The transformation of Landak Tourist Park into an ecotourism site requires several strategies, including the development of eco-friendly infrastructure, local community empowerment, improved accessibility, eco-friendly facilities, and natural resource management.